Peran Strategis Guru Mentor Dalam Program Pengalaman Lapangan [The Strategic Role of the Teacher Mentor in a Field Experience Program] - Lastiar Roselyna Sitompul (Universitas Pelita Harapan, 2017)
The field experience is an important aspect of a student's academic program in improving the quality of a graduate of a teacher education program. The mentor teacher has a strategic role in developing students' competence to be a professional teacher. To know the mentor teacher's role and the process of guidance during the field experience program, student teachers need to observe, interview and make a portfolio. The results of the study indicates that there are obstacles in the field supervision process such as the limited opportunities for guidance because of the many duties that must be done by the mentor teachers. It is hoped that this article will provide advice to the Teachers College as the organizer of the field experience program to improve the socialization of the role of mentor teachers in schools where field experience programs are held, so that such programs will be more effective in achieving the expected goals.BAHASA INDONESIA ABSTRAK: Program pengalaman lapangan (PPL) adalah salah satu program mata kuliah yang berorientasi pada pengalaman mengajar di lapangan yang sangat penting dalam meningkatkan mutu seorang lulusan fakultas ilmu pendidikan. Guru mentor mempunyai peran strategis dalam mengembangkan kemampuan kompetensi mahasiswa guru untuk siap menjadi seorang guru yang profesional. Untuk mengetahui peran dan proses pembimbingan selama program pengalaman lapangan dilakukan penelitian deskriptif melalui observasi dan wawancara serta menggunakan dokumen portofolio mahasiswa PPL. Hasil observasi menunjukkan ditemukan kendala-kendala dalam proses pembimbingan di lapangan seperti terbatasnya kesempatan bimbingan oleh karena tugas dan kewajiban yang lain yang harus dikerjakan para guru mentor. Diharapkan melalui artikel ini Teachers College sebagai penyelenggara program pengalaman lapangan lebih meningkatkan sosialisasi peran guru mentor di sekolah-sekolah tempat diadakannya program pengalaman lapangan, sehingga semakin efektif untuk mencapai tujuan yang diharapkan.